STRATEGI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DALAM KEMAMPUAN KOMUNIKASI TINGKAT SD/MI - Indriani; Anwar Sidik (Eskul : Jurnal Pengajaran dan Pengembangan Sekola, 2026)
This study aims to analyze the role of Civics Education (PKn) in improving the communication skills of elementary and Islamic elementary school students (SD/MI). The background of the research stems from the urgency of communication as the core of the educational process and as a means of shaping national character. The research method employs a qualitative approach through a literature review of various relevant sources. The findings show that Civics Education plays a strategic role in fostering speaking ability, building self-confidence, and shaping critical and democratic attitudes. Interactive learning strategies such as open questioning, group discussions, deliberation simulations, simple presentations, storytelling, and the use of basic technology prove effective in developing students’ communication skills. Challenges such as passivity, limited vocabulary, and the dominance of lecture methods can be addressed through the teacher’s role as a facilitator who creates a supportive, democratic, and appreciative classroom atmosphere. The conclusion emphasizes that Civics Education is not merely a cognitive subject but also a medium for forming communicative, participatory, and democratic character relevant to global demands. This study also opens opportunities to develop more innovative Civics learning models by utilizing digital technology to meet communication challenges in the modern era.